A gel polymer electrolyte and a preparation method and application thereof

CN123018123APending Publication Date: 2026-10-30TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611517365.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0002]随着低温储能、极地科考、航空航天、寒区电动装备及低温电子设备等领域的快速发展,对能够在极端低温条件下稳定运行的电化学储能器件提出了迫切需求;电池作为核心供能单元,其低温性能直接决定了整个系统的可靠性和应用范围;然而,传统电池在低温环境下通常面临电解质黏度急剧升高、离子电导率显著下降、电极/电解质界面电荷转移动力学严重迟缓等一系列问题,导致电池容量大幅衰减、倍率性能恶化,甚至完全丧失充放电能力;因此,开发适用于低温环境的新型高安全性、高离子传导能力的电解质体系,已成为当前电化学储能领域亟待解决的关键技术难题

Benefits of technology

本发明提出一种凝胶聚合物电解质及其制备方法与应用,通过在原位聚合制备凝胶聚合物电解质的体系中,创造性地引入链转移剂组分并与路易斯酸引发剂协同作用,实现了对环醚单体开环聚合过程和聚合物网络结构的有效调控;链转移剂在聚合过程中通过链转移反应,使原有增长的聚合物链终止并产生新的活性中心继续引发聚合,从而在不降低单体转化率的前提下,显著增加了聚合物链的数量,降低了聚合物链的平均长度,减少了链间缠结程度,增加了聚合物网络的自由体积;这一结构优化直接提升了钠离子在聚合物网络中的传输动力学性能,使所得凝胶聚合物电解质在低温(如-30℃)下仍能保持高达0.25mS·cm-1的优异离子电导率;同时,低缠结或非缠结的聚合物网络结构有助于在电极表面形成薄而均匀、结构稳定的固态电解质界面相,显著降低了界面阻抗,改善了钠离子在电极/电解质界面的传输能力;将该电解质应用于钠离子电池中,在-20℃低温条件下,电池容量保持率接近100%,展现出优异的循环稳定性和倍率充放电性能;此外,本发明的制备方法为原位聚合,工艺简单、条件温和、反应时间短,无需额外的溶剂处理和复杂的后处理工序,安全高效,非常适合工业化生产和实际储能器件中的应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018123A_ABST
    Figure CN123018123A_ABST
Patent Text Reader

Abstract

The application discloses a kind of gel polymer electrolyte and its preparation method and application;The gel polymer electrolyte is formed by in-situ polymerization reaction from cyclic ether monomer, sodium salt, plasticizer, Lewis acid initiator and chain transfer agent;Chain transfer agent is used to control polymer chain length to increase polymer network free volume, increase the number of polymer chains, reduce the average chain length and reduce interchain entanglement by chain transfer reaction, thereby improving the sodium ion transport capacity;Preparation method is: sodium salt, monomer and plasticizer are mixed to obtain liquid precursor;Lewis acid is mixed with chain transfer agent to obtain initiation-chain transfer solution;After mixing, in-situ ring-opening polymerization is carried out to obtain the electrolyte;The ionic conductivity of the electrolyte reaches 0.25 mS·cm ‑1 At-30℃, the capacity retention rate of the assembled battery is close to 100%, and excellent low-temperature cycle stability and rate performance are exhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of electrolyte materials for sodium-ion batteries, specifically relating to a gel polymer electrolyte, its preparation method, and its application. Background Technology

[0002] With the rapid development of cryogenic energy storage, polar scientific research, aerospace, cold-region electric equipment, and cryogenic electronic equipment, there is an urgent need for electrochemical energy storage devices that can operate stably under extreme low-temperature conditions. As the core power supply unit, the low-temperature performance of the battery directly determines the reliability and application range of the entire system. However, traditional batteries usually face a series of problems in low-temperature environments, such as a sharp increase in electrolyte viscosity, a significant decrease in ionic conductivity, and a severe slowdown in charge transfer kinetics at the electrode / electrolyte interface. This leads to a significant decrease in battery capacity, a deterioration in rate performance, and even a complete loss of charge and discharge capability. Therefore, developing a new electrolyte system with high safety and high ion conductivity suitable for low-temperature environments has become a key technical challenge that urgently needs to be solved in the field of electrochemical energy storage.

[0003] Sodium-ion batteries, with their advantages of abundant and widely distributed sodium resources, low cost, and similar working principle to lithium-ion batteries, are considered one of the ideal choices for next-generation large-scale energy storage and power batteries for specific scenarios. However, similar to lithium-ion batteries, sodium-ion batteries also suffer from significant performance degradation at low temperatures. At low temperatures, the migration rate of sodium ions in the electrolyte phase and the desolvation and charge transfer kinetics at the electrode / electrolyte interface all slow down significantly, and the interfacial impedance increases sharply. This directly limits the low-temperature capacity retention, cycle stability, and rate charge-discharge performance of sodium-ion batteries. Among these, the insufficient low-temperature ion transport capacity and poor interfacial stability of the electrolyte material are the two core bottlenecks restricting the improvement of the low-temperature performance of sodium-ion batteries.

[0004] Among numerous electrolyte systems, gel polymer electrolytes combine the high ionic conductivity of liquid electrolytes with the high safety and non-flow properties of solid polymer electrolytes, making them a promising quasi-solid electrolyte system. Compared to all-solid polymer electrolytes, gel polymer electrolytes contain liquid plasticizer components, which can effectively reduce the crystallinity and glass transition temperature of the polymer system and enhance the mobility of polymer chain segments, thus facilitating ion transport at low temperatures. Nevertheless, in extreme low-temperature environments, the inherent inter-chain entanglement structure of the polymer network in existing gel polymer electrolytes still severely restricts chain segment movement, limiting efficient ion conduction and resulting in ionic conductivity that still falls short of practical application requirements. Furthermore, the interfacial compatibility and stability between the electrode and the electrolyte need further improvement. Therefore, it is urgent to develop a novel gel polymer electrolyte material and a simple and efficient preparation method that can fundamentally improve low-temperature ion transport capabilities and interfacial properties from the perspective of polymer network structure design. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a gel polymer electrolyte, its preparation method and application.

[0006] To achieve the above objectives, the present invention provides the following technical solution: This application provides a gel polymer electrolyte comprising a product formed by in-situ polymerization of the following raw materials: Polymer monomers, wherein the polymer monomers are cyclic ether monomers; Sodium salts are used to provide sodium ions; Plasticizers; Lewis acids, as initiators; and Chain transfer agents are used to modulate polymer chain length to increase the free volume of polymer networks.

[0007] Optionally, the cyclic ether monomer is selected from at least one of 1,3-dioxopentane, ethylene oxide, oxetane, and tetrahydrofuran; The sodium salt is selected from at least one of sodium bis(trifluoromethylsulfonyl)imide, sodium hexafluorophosphate, sodium perchlorate, sodium bis(fluorosulfonyl)imide, and sodium tetrafluoroborate.

[0008] Optionally, the plasticizer is selected from at least one of fluoroethylene carbonate, propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, and N,N-dimethylformamide.

[0009] Optionally, the chain transfer agent is selected from at least one of tetrahydrofuran, n-dodecyl mercaptan, carbon tetrachloride, and isopropanol, and the amount of the chain transfer agent is 1% to 1.2% of the total amount of the polymer monomers.

[0010] Optionally, the Lewis acid is selected from at least one of triethylborane, boron trifluoride, alkylaluminum, phosphorus pentafluoride, and antimony pentachloride.

[0011] A method for preparing the above-mentioned gel polymer electrolyte includes the following steps: S1. Mix sodium salt, cyclic ether polymer monomer and plasticizer to obtain liquid precursor electrolyte; S2. Mix the Lewis acid and the chain transfer agent to obtain an initiator-chain transfer mixed solution; S3. The initiator-chain transfer mixed solution is added to the liquid precursor electrolyte, and after mixing evenly, in-situ ring-opening polymerization is carried out to obtain the gel polymer electrolyte.

[0012] Optionally, the molar ratio of the sodium salt, cyclic ether polymer monomer, and plasticizer is 1:(11-12):(2.8-2.9); and the volume percentage of the plasticizer in the liquid precursor electrolyte is 15%-25%.

[0013] Optionally, the volume ratio of the Lewis acid to the chain transfer agent is 1:(80-120); the amount of the initiator-chain transfer mixed solution added is 0.01wt% to 0.015wt% based on the total mass of the liquid precursor electrolyte.

[0014] Optionally, by controlling the type and / or amount of the chain transfer agent, the number of polymer chains, the average chain length, and the degree of interchain entanglement in the ether polymer network generated by the polymerization reaction can be increased.

[0015] An application of a gel polymer electrolyte, which is used to prepare a low-temperature sodium-ion battery, the low-temperature sodium-ion battery further comprising a positive electrode, a negative electrode, and a separator.

[0016] Compared with the prior art, this application has the following beneficial effects: This invention proposes a gel polymer electrolyte, its preparation method, and its applications. By creatively introducing a chain transfer agent component into the in-situ polymerization system for preparing the gel polymer electrolyte, and synergistically interacting with a Lewis acid initiator, effective control over the ring-opening polymerization process of cyclic ether monomers and the polymer network structure is achieved. During polymerization, the chain transfer agent terminates the existing growing polymer chains through a chain transfer reaction, generating new active centers to continue initiating polymerization. This significantly increases the number of polymer chains, reduces the average length of the polymer chains, decreases the degree of interchain entanglement, and increases the free volume of the polymer network without reducing the monomer conversion rate. This structural optimization directly improves the transport kinetics of sodium ions in the polymer network, enabling the resulting gel polymer electrolyte to maintain a high 0.25 mS·cm at low temperatures (e.g., -30°C). -1The electrolyte exhibits excellent ionic conductivity. Simultaneously, the low-entanglement or non-entanglement polymer network structure facilitates the formation of a thin, uniform, and structurally stable solid electrolyte interface phase on the electrode surface, significantly reducing interfacial impedance and improving the transport capability of sodium ions at the electrode / electrolyte interface. When applied to sodium-ion batteries, the battery capacity retention rate is close to 100% at -20℃, demonstrating excellent cycle stability and rate charge / discharge performance. Furthermore, the preparation method of this invention is in-situ polymerization, which is simple, mild, and has a short reaction time, requiring no additional solvent treatment or complex post-processing steps. It is safe and efficient, making it highly suitable for industrial production and practical energy storage device applications. Attached Figure Description

[0017] Figure 1 This is a schematic diagram illustrating the mechanism of in-situ polymerization of Lewis acids and monomers according to the present invention. Figure 2 The infrared spectrum of the in-situ polymerized sample of this invention; Figure 3 A photograph of a pouch battery fabricated for an example embodiment; Figure 4 The diagram shows the ionic conductivity of the in-situ polymerized sample of the present invention at different temperatures. Figure 5 A comparison chart of the capacity of batteries assembled with electrolytes from the examples and several comparative examples under different discharge rates; Figure 6 Cyclic performance graph of a low-temperature battery fabricated for an example. Detailed Implementation

[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0019] Furthermore, in this invention, an element referred to as fixed to or disposed on another element may be directly disposed on the other element, or there may be an intermediate element. When an element is considered to be connected to another element, it may be directly connected to the other element, or there may be an intermediate element present simultaneously. The terms vertical, horizontal, left, right, and similar expressions used herein are for illustrative purposes only and do not represent the only possible implementation.

[0020] Example 1 See Figures 1-6 This application provides a gel polymer electrolyte comprising a product formed by in-situ polymerization of the following raw materials: Polymer monomers, wherein the polymer monomers are cyclic ether monomers; Sodium salts are used to provide sodium ions; Plasticizers; Lewis acids, as initiators; and Chain transfer agents are used to modulate polymer chain length to increase the free volume of polymer networks; This embodiment provides a gel polymer electrolyte comprising a product formed by in-situ polymerization of a polymer monomer, a sodium salt, a plasticizer, a Lewis acid, and a chain transfer agent. The polymer monomer is 1,3-dioxapentane (DOL), a cyclic ether monomer. The sodium salt is sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), used to provide conductive sodium ions in the system. The plasticizer is fluoroethylene carbonate (FEC), which enhances the mobility of polymer chains and improves the compatibility of the electrode / electrolyte interface. The Lewis acid is boron trifluoride (BF3), used as an initiator to initiate the ring-opening polymerization of the cyclic ether monomer. The chain transfer agent is tetrahydrofuran (THF), whose core function is to regulate the polymer chain length during the ring-opening polymerization of DOL, thereby increasing the free volume of the final polymer network.

[0021] In the preparation process, 0.909 g of NaTFSI sodium salt, which had been vacuum dried at 105℃, was first completely dissolved in a mixed solution of DOL and FEC at a volume ratio of 8:2. The solution was stirred until homogeneous and clear to obtain a liquid precursor electrolyte. Subsequently, sodium flakes were added and the mixture was allowed to stand to remove residual trace amounts of water. Boron trifluoride and tetrahydrofuran were then mixed at a volume ratio of 1:100 and stirred until homogeneous to obtain an initiator-chain transfer mixed solution. This initiator-chain transfer mixed solution was added to the liquid precursor electrolyte at a ratio of 0.012 wt% of the total mass of the liquid precursor electrolyte. After rapid stirring until homogeneous, the mixture was allowed to stand at room temperature for in-situ ring-opening polymerization. The reaction was completed quickly, and the liquid precursor completely solidified to obtain a colorless and transparent gel polymer electrolyte. Infrared spectroscopy (e.g.) was performed. Figure 2 The results (shown) confirm the successful execution of the DOL ring-opening polymerization reaction, and the characteristic peaks of NaTFSI and FEC remain intact, indicating that they were successfully immobilized in the polymer network.

[0022] Regarding the mechanism of action of the chain transfer agent tetrahydrofuran, such as Figure 1As shown: Lewis acid BF3 first coordinates with the oxygen atom in the cyclic ether monomer DOL, weakening the CO bond within the ring, promoting ring opening and forming an active oxygen ononium salt growth center, thereby initiating a chain growth reaction. When tetrahydrofuran is also present in the system, as a powerful chain transfer agent, tetrahydrofuran can undergo a chain transfer reaction with the end of the growing active oxygen ononium salt chain. Specifically, the active growing chain undergoes a chain termination-transfer process from the tetrahydrofuran molecule, terminating itself into a shorter polymer chain, while the tetrahydrofuran molecule transforms into a new active oxygen ononium salt center, continuing to initiate the polymerization of new DOL monomers. This chain transfer process continues cyclically throughout the polymerization reaction, resulting in a significantly increased number of poly(1,3-dioxopentane) segments with a significantly shortened average length in the polymer system while maintaining monomer conversion. This change in chain structure directly leads to a significant reduction in the interchain entanglement density of the polymer network and an effective increase in free volume, creating a more unobstructed conduction channel for the rapid migration of sodium ions.

[0023] The gel polymer electrolyte prepared in this embodiment was assembled into a sodium-ion battery for performance testing. The battery assembly method was as follows: aluminum foil coated with sodium vanadium phosphate (Na3V2(PO4)3) was used as the positive electrode, sodium metal sheet as the negative electrode, and glass fiber membrane as the separator. The separator was placed between the positive and negative electrodes, and liquid precursor electrolyte and initiation-chain transfer mixed solution were injected. After sealing, in-situ polymerization was completed inside the battery to obtain an integrated low-temperature sodium-ion battery. The actual soft-pack battery is shown in the figure. Figure 3 As shown.

[0024] The ionic conductivity of the electrolyte in this embodiment was tested at different temperatures, and the results are as follows: Figure 4 As shown, thanks to the low-entanglement polymer network structure regulated by the chain transfer agent, this electrolyte exhibits excellent low-temperature ion conductivity, maintaining an ion conductivity as high as 0.25 mS·cm even at extreme low temperatures of -30°C. -1 .

[0025] In one specific embodiment, the cyclic ether monomer is selected from at least one of 1,3-dioxopentane, ethylene oxide, oxetane, and tetrahydrofuran.

[0026] The sodium salt is selected from at least one of sodium bis(trifluoromethylsulfonyl)imide, sodium hexafluorophosphate, sodium perchlorate, sodium bis(fluorosulfonyl)imide, and sodium tetrafluoroborate.

[0027] Regarding cyclic ether monomers, in addition to 1,3-dioxapentane, any one of ethylene oxide, oxetane, and tetrahydrofuran can be selected, or several of the above monomers can be selected simultaneously for copolymerization. Different cyclic ether monomers have different chain segment structures and flexibility after ring-opening polymerization, which can be flexibly selected according to actual needs, but all of them can undergo ring-opening polymerization under Lewis acid initiation and achieve effective control of polymer network structure in the presence of chain transfer agent. Regarding sodium salts, in addition to sodium bis(trifluoromethanesulfonyl)imide, any one or several of sodium hexafluorophosphate, sodium perchlorate, sodium bis(fluorosulfonyl)imide, and sodium tetrafluoroborate can be selected. All of the above sodium salts can effectively dissociate sodium ions in the gel polymer electrolyte system to provide charge carriers for the system. Their types and combinations can be selected according to the specific requirements for ionic conductivity, electrochemical window, and interfacial compatibility. It should be noted that when different sodium salts are used, their dissolution behavior in liquid precursor electrolytes and the performance of the final gel electrolyte may differ. Those skilled in the art can adjust the dosage according to the actual situation.

[0028] In one specific embodiment, the plasticizer is selected from at least one of fluoroethylene carbonate, propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, and N,N-dimethylformamide.

[0029] In this embodiment, the core function of the plasticizer is to reduce the interaction forces between polymer chains, improve the mobility of chain segments, and improve the interfacial compatibility between the electrolyte and the electrode. In addition to the selected fluoroethylene carbonate, the plasticizer can also be selected from any one or more of propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, and N,N-dimethylformamide. Fluoroethylene carbonate is preferred due to its good film-forming properties and low-temperature performance, while other types of carbonate or amide plasticizers can also reduce the glass transition temperature of the system to a certain extent and improve the ionic conductivity under low-temperature conditions. The type and amount of plasticizer can be adaptively adjusted according to the specific polymer monomer and sodium salt system.

[0030] In one specific embodiment, the chain transfer agent is selected from at least one of tetrahydrofuran, n-dodecyl mercaptan, carbon tetrachloride, and isopropanol, and the amount of the chain transfer agent is 1% to 1.2% of the total amount of the polymer monomers.

[0031] In this embodiment, the chain transfer agent is a key component for achieving the core technical effect of the present invention. In addition to tetrahydrofuran, it can also be selected from any one or more of n-dodecyl mercaptan, carbon tetrachloride, and isopropanol. Different types of chain transfer agents have different abilities to regulate polymer chain length due to differences in their chain transfer constants, but they can all increase the number of polymer chains, reduce the average chain length, and reduce inter-chain entanglement through chain transfer reactions. Regarding the dosage of the chain transfer agent, the present invention has found through experimental research that when its dosage is 1% to 1.2% of the total polymer monomer, the best balance can be achieved between the polymerization reaction rate, monomer conversion rate, and chain length regulation effect. When the dosage is too low, the chain transfer effect is not significant, and the polymer network may still have a lot of entanglement. When the dosage is too high, it may lead to the polymer chain being too short, affecting the overall mechanical properties and structural stability of the gel electrolyte. The dosage of tetrahydrofuran roughly corresponds to this preferred range, thus obtaining excellent low-temperature ion conduction performance.

[0032] In one specific embodiment, the Lewis acid is selected from at least one of triethylborane, boron trifluoride, alkyl aluminum, phosphorus pentafluoride, and antimony pentachloride.

[0033] In this embodiment, Lewis acids are used as initiators for the ring-opening polymerization of cyclic ether monomers. Their mechanism of action lies in their ability to coordinate with oxygen atoms in the cyclic ether monomer, weakening the CO bond, thereby promoting ring opening and forming active growth centers. In addition to boron trifluoride, Lewis acids can also be selected from any one or more of triethylborane, alkylaluminum, phosphorus pentafluoride, and antimony pentachloride. Different Lewis acids have different acidity and coordination abilities, which directly affect the initiation efficiency and polymerization rate, but their fundamental mechanism for initiating ring-opening polymerization is the same. In practical applications, the appropriate type of Lewis acid can be selected according to the required polymerization rate and the requirements for electrolyte purity.

[0034] A method for preparing a gel polymer electrolyte includes the following steps: S1. Mix sodium salt, cyclic ether polymer monomer and plasticizer to obtain liquid precursor electrolyte; S2. Mix the Lewis acid and the chain transfer agent to obtain an initiator-chain transfer mixed solution; S3. The initiator-chain transfer mixed solution is added to the liquid precursor electrolyte, and after mixing evenly, in-situ ring-opening polymerization is carried out to obtain the gel polymer electrolyte.

[0035] In this embodiment, the preparation method includes three core steps; step S1 is to prepare a liquid precursor electrolyte, that is, to mix sodium salt, cyclic ether polymer monomer and plasticizer evenly; the specific operation of this step is as follows: at room temperature, 0.909g of bis(trifluoromethanesulfonyl)imine sodium salt that has been vacuum dried at 105℃ is completely dissolved in a mixed solution composed of 1,3-dioxane and fluoroethylene carbonate in a volume ratio of 8:2, and stirred until a clear and homogeneous solution is formed.

[0036] Step S2 involves preparing an initiation-chain transfer mixed solution, which involves mixing a Lewis acid and a chain transfer agent. The specific steps are as follows: at room temperature, boron trifluoride and tetrahydrofuran are mixed at a volume ratio of 1:100 and stirred until homogeneous to obtain the initiation-chain transfer mixed solution.

[0037] Step S3 is in-situ polymerization, which involves adding the initiator-chain transfer mixed solution to the liquid precursor electrolyte, mixing it evenly, and then carrying out in-situ ring-opening polymerization. The specific operation of this step is as follows: the initiator-chain transfer mixed solution is added at a ratio of 0.012 wt% of the total mass of the liquid precursor electrolyte, and after rapid stirring and even mixing, the reaction is allowed to stand at room temperature. The polymerization can be completed in a short time to obtain the gel polymer electrolyte.

[0038] This method can complete all operations at room temperature without additional heating or special equipment. It is simple, has a short reaction time, is safe and efficient, and is suitable for in-situ polymerization inside batteries.

[0039] In one specific embodiment, the molar ratio of the sodium salt, the cyclic ether polymer monomer, and the plasticizer is 1:(11-12):(2.8-2.9); the volume percentage of the plasticizer in the liquid precursor electrolyte is 15%-25%.

[0040] In this embodiment, the molar ratio of sodium bis(trifluoromethanesulfonyl)imide, 1,3-dioxane, and fluoroethylene carbonate is controlled to be approximately 1:11.5:2.8, which falls within the range of 1:(11-12):(2.8-2.9). Simultaneously, the volume percentage of fluoroethylene carbonate in the liquid precursor electrolyte is 20%, falling within the preferred range of 15%-25%. This ratio ensures sufficient dissolution of the sodium salt, effective function of the plasticizer, and appropriate monomer concentration, providing a good foundation for subsequent polymerization reactions and the formation of the gel network structure.

[0041] In one specific embodiment, the volume ratio of the Lewis acid to the chain transfer agent is 1:(80-120); the amount of the initiator-chain transfer mixed solution added is 0.01wt% to 0.015wt% based on the total mass of the liquid precursor electrolyte.

[0042] In this embodiment, the volume ratio of boron trifluoride to tetrahydrofuran is 1:100, falling within the range of 1:(80-120); the amount of the initiator-chain transfer mixed solution added is 0.012wt% of the total mass of the liquid precursor electrolyte, falling within the range of 0.01wt% to 0.015wt%. This ratio and amount can ensure that the polymerization reaction proceeds smoothly at an appropriate rate and achieve effective control of the polymer chain length, while avoiding adverse effects on electrolyte performance from initiator residue or excessive chain transfer agent.

[0043] In one specific embodiment, by controlling the type and / or amount of the chain transfer agent, the number of polymer chains, the average chain length, and the degree of interchain entanglement in the ether polymer network generated by the polymerization reaction are increased.

[0044] In this embodiment, by selecting tetrahydrofuran as the chain transfer agent and controlling its dosage, precise control of the network structure of the polymerization product was achieved. Specifically, compared to the comparative system without a chain transfer agent, the polymer network obtained in this embodiment showed a significant increase in the number of polymer chains, a significant decrease in average chain length, and a substantial reduction in interchain entanglement. This structural characteristic can be verified by characterizing the extracted polymer using gel permeation chromatography and other methods, and is directly reflected in its macroscopic properties, exhibiting a high 0.25 mS·cm at -30°C. -1 It has excellent ionic conductivity.

[0045] A low-temperature sodium-ion battery includes a positive electrode, a negative electrode, a separator, and an electrolyte disposed between the positive and negative electrodes, wherein the electrolyte is a gel polymer electrolyte.

[0046] In this embodiment, the battery is assembled as follows: aluminum foil coated with sodium vanadium phosphate is used as the positive electrode, sodium metal sheet is used as the negative electrode, and glass fiber membrane is used as the separator; the separator is placed between the positive and negative electrodes, liquid precursor electrolyte and initiation-chain transfer mixed solution are injected, and after sealing, in-situ polymerization is completed inside the battery to obtain an integrated low-temperature sodium-ion battery product. The actual soft-pack battery is shown in the image. Figure 3 As shown.

[0047] Electrochemical performance tests were conducted on this low-temperature sodium-ion battery; discharge tests at different rates were performed at -20℃, and the results are as follows: Figure 5As shown; to demonstrate the technical effect of the present invention, two comparative batteries were also prepared. Comparative Example 1 used a conventional liquid electrolyte, that is, 0.168g of sodium hexafluorophosphate was completely dissolved in 1000μL of diethylene glycol dimethyl ether to prepare a liquid electrolyte, and sacrificial sodium sheets were used to treat trace amounts of moisture. Comparative Example 2 used a gel polymer electrolyte without the introduction of chain transfer agents, that is, 0.909g of sodium bis(trifluoromethanesulfonyl)imine was completely dissolved in a mixed solution composed of 1,3-dioxane and fluoroethylene carbonate in a volume ratio of 8:2, and sacrificial sodium sheets were used to treat trace amounts of moisture, but tetrahydrofuran was not added. Chain transfer agent; Test results show that although the conventional liquid electrolyte battery of Comparative Example 1 has acceptable performance at room temperature, its capacity and rate performance degrade severely under low temperature conditions; The gel electrolyte battery of Comparative Example 2 without the introduction of chain transfer agent has a significantly lower discharge capacity at all rates than that of this embodiment due to severe polymer network entanglement, small free volume, and high ion transport resistance; In contrast, this embodiment, due to the introduction of chain transfer agent, forms a low-entanglement polymer network, which greatly promotes sodium ion transport and improves interfacial dynamics, exhibiting the highest discharge capacity at all rates such as 0.5C, 1C, 2C, and 5C.

[0048] The cycling performance test results under -20℃ low temperature conditions are as follows: Figure 6 As shown, during charge-discharge cycling at a 1C rate, the battery in this embodiment maintained an initial discharge capacity retention rate close to 100%, and exhibited minimal capacity decay after prolonged cycling. The coulombic efficiency remained consistently at a high level close to 100%, demonstrating excellent low-temperature cycling stability. This superior performance stems from the dual contribution of the low-entanglement polymer network: on the one hand, it enhances the sodium ion transport capability of the electrolyte bulk phase; on the other hand, it helps to form a stable, uniform, and low-resistance solid electrolyte interface film on the surfaces of the sodium metal anode and sodium vanadium phosphate cathode, effectively suppressing interfacial side reactions and maintaining the long-term stability of the interface structure.

[0049] The performance comparison between the above embodiments and comparative examples fully demonstrates that the present invention successfully constructs a gel polymer electrolyte with low entanglement and high free volume by introducing a chain transfer agent, fundamentally solving the problem of slow ion conduction of conventional gel electrolytes at low temperatures.

[0050] Example 2 This embodiment provides a chain transfer agent-regulated gel polymer electrolyte for low-temperature sodium-ion batteries, its in-situ preparation method, and its application. The specific process is as follows: At room temperature, 0.909 g of sodium bis(trifluoromethanesulfonyl)imide (NaTFSI) salt was completely dissolved in a mixed solution of 1,3-dioxane (DOL) and fluoroethylene carbonate (FEC) in a volume ratio of 8:2. The solution was stirred until a clear and homogeneous liquid precursor electrolyte was formed. NaTFSI was vacuum dried at 105°C before use to remove trace amounts of moisture. The molar ratio of NaTFSI, DOL, and FEC was controlled at approximately 1:11.5:2.8, with FEC comprising 20% ​​of the total volume of the liquid precursor electrolyte. The solution was then allowed to stand with the addition of sacrificial sodium flakes to further remove impurities. The remaining trace amount of moisture; in addition, at room temperature, boron trifluoride (BF3) as a Lewis acid initiator and tetrahydrofuran (THF) as a chain transfer agent are mixed at a volume ratio of 1:100 and stirred evenly to obtain an initiation-chain transfer mixed solution; then, the initiation-chain transfer mixed solution is added to the aforementioned liquid precursor electrolyte at a ratio of 0.012 wt% of the total mass of the liquid precursor electrolyte, and after rapid stirring evenly, the mixture is allowed to stand at room temperature to carry out an in-situ ring-opening polymerization reaction; the reaction proceeds rapidly at room temperature, and the liquid precursor is completely solidified in a short time to obtain a colorless and transparent chain transfer agent-regulated gel polymer electrolyte.

[0051] The core technology of this embodiment lies in the introduction of the chain transfer agent THF and its synergistic effect with the initiator BF3; Figure 1 The mechanism of in-situ polymerization of Lewis acids and monomers is illustrated. Lewis acid BF3 first coordinates with the oxygen atom in the cyclic ether monomer DOL, weakening the CO bond, promoting ring opening, and forming an active oxygen ononium salt growth center, initiating a chain growth reaction. At this point, THF, acting as a chain transfer agent, reacts with the end of the growing active oxygen ononium salt chain, terminating the original growing chain into a shorter polymer chain. Simultaneously, the THF molecule transforms into a new active oxygen ononium salt center, continuing to initiate the polymerization of new DOL monomers. This process continuously cycles within the polymerization system, resulting in a significantly increased number and shortened average length of poly(1,3-dioxopentane) segments while maintaining monomer conversion. This change in chain structure directly leads to a substantial reduction in the interchain entanglement density of the polymer network and an effective increase in free volume, providing a more unobstructed channel for the rapid conduction of sodium ions. Figure 2 The infrared spectrum of the in-situ polymerized sample obtained in this embodiment is shown. In the spectrum, the characteristic absorption peaks of the DOL monomers disappeared or weakened significantly after polymerization, while characteristic absorption peaks corresponding to the long polyether chains appeared, confirming the successful ring-opening polymerization reaction of DOL. In addition, the characteristic peaks attributed to NaTFSI and FEC still exist, indicating that they were successfully fixed in the gel polymer network as electrolyte salts and plasticizers.

[0052] The above-mentioned gel polymer electrolyte is applied to sodium-ion batteries; the battery assembly uses aluminum foil coated with sodium vanadium phosphate (Na3V2(PO4)3, NVP) as the positive electrode, sodium metal sheet as the negative electrode, and glass fiber membrane as the separator; the separator is placed between the positive and negative electrodes, the liquid precursor electrolyte prepared in the above steps is injected, and then the initiation-chain transfer mixed solution is injected. After sealing, in-situ polymerization is completed inside the battery to obtain an integrated low-temperature sodium-ion battery; Figure 3 A photograph of a pouch cell battery manufactured using this method is shown, demonstrating the practicality and scale-up potential of the method.

[0053] The performance of the gel polymer electrolyte and battery prepared in this embodiment was tested; Figure 4 The ionic conductivity of the electrolyte at different temperatures is shown. AC impedance spectroscopy was used for testing, and the results indicate that, thanks to the low-entanglement polymer network structure regulated by the chain transfer agent, the electrolyte exhibits excellent low-temperature ionic conductivity, maintaining a high ionic conductivity of 0.25 mS·cm even at extreme low temperatures of -30°C. -1 The results far exceeded those of the control gel electrolyte system without the introduction of chain transfer agents, fully demonstrating the decisive role of chain transfer agents in improving low-temperature ion transport capabilities.

[0054] For comparison, the following comparative examples were also prepared: Comparative Example 1 was a traditional liquid electrolyte system: at room temperature, 0.168 g of sodium hexafluorophosphate (NaPF6) was completely dissolved in 1000 μL of diethylene glycol dimethyl ether to form a liquid electrolyte, and trace amounts of moisture were removed by standing treatment with sacrificial sodium sheets; Comparative Example 2 was a gel polymer electrolyte system without the introduction of chain transfer agent: at room temperature, 0.909 g of NaTFSI salt was completely dissolved in a mixed solution of DOL and FEC in a volume ratio of 8:2 to form a liquid electrolyte, and trace amounts of moisture were removed by standing treatment with sacrificial sodium sheets, but no THF chain transfer agent was added (or only BF3 initiator was added without THF).

[0055] Figure 5 The comparison of the discharge capacity of batteries assembled with the electrolytes of this embodiment and the comparative example at different rates under -20°C is shown. Although the conventional liquid electrolyte battery of Comparative Example 1 has good performance at room temperature, its capacity and rate performance are severely degraded at low temperatures. The gel polymer electrolyte of Comparative Example 2 without the introduction of chain transfer agent has severe polymer network entanglement, small free volume, and high ion transport resistance. Therefore, its discharge capacity at all rates is significantly lower than that of this embodiment. In contrast, this embodiment, due to the introduction of the chain transfer agent THF, forms a low-entanglement polymer network structure, which greatly promotes sodium ion transport and improves the electrode / electrolyte interface dynamics. It exhibits the highest discharge capacity at all rates, including 0.5C, 1C, 2C, and 5C, demonstrating excellent rate charge-discharge performance.

[0056] Figure 6 The cycling performance of the low-temperature battery fabricated in this embodiment at -20°C is shown. Charge-discharge cycle tests at 1C rate show that the battery retains nearly 100% of its initial discharge capacity, exhibits minimal capacity decay after prolonged cycling, and maintains a high coulombic efficiency consistently close to 100%, demonstrating excellent low-temperature cycling stability. This superior performance stems from the dual contribution of the low-entanglement polymer network: on the one hand, it enhances the sodium ion transport capacity of the electrolyte bulk phase; on the other hand, it helps form a stable, uniform, and low-resistance solid electrolyte interface film on the surfaces of the sodium metal anode and sodium vanadium phosphate cathode, effectively suppressing interfacial side reactions and maintaining the long-term stability of the interface structure.

[0057] The performance comparison test results of the above embodiments and comparative examples strongly demonstrate that the present invention successfully constructs a gel polymer electrolyte with low entanglement and high free volume through the synergistic effect of chain transfer agent and Lewis acid, fundamentally solving the core problem of slow ion conduction of conventional gel electrolytes at low temperatures. The chain transfer agent plays a creative and irreplaceable role in improving the low-temperature performance of the electrolyte.

[0058] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.

[0059] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A gel polymer electrolyte, characterized in that, Includes products formed from the following raw materials through in-situ polymerization: Polymer monomers, wherein the polymer monomers are cyclic ether monomers; Sodium salts are used to provide sodium ions; Plasticizers; Lewis acids, as initiators; and Chain transfer agents are used to modulate polymer chain length to increase the free volume of polymer networks.

2. The gel polymer electrolyte according to claim 1, characterized in that, The cyclic ether monomers are selected from at least one of 1,3-dioxopentane, ethylene oxide, oxetane, and tetrahydrofuran; The sodium salt is selected from at least one of sodium bis(trifluoromethylsulfonyl)imide, sodium hexafluorophosphate, sodium perchlorate, sodium bis(fluorosulfonyl)imide, and sodium tetrafluoroborate.

3. The gel polymer electrolyte according to claim 1, characterized in that, The plasticizer is selected from at least one of fluoroethylene carbonate, propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, and N,N-dimethylformamide.

4. The gel polymer electrolyte according to claim 1, characterized in that, The chain transfer agent is selected from at least one of tetrahydrofuran, n-dodecyl mercaptan, carbon tetrachloride, and isopropanol, and the amount of the chain transfer agent is 1% to 1.2% of the total amount of the polymer monomers.

5. The gel polymer electrolyte according to claim 1, characterized in that, The Lewis acid is selected from at least one of triethylborane, boron trifluoride, alkyl aluminum, phosphorus pentafluoride, and antimony pentachloride.

6. A method for preparing the gel polymer electrolyte according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1. Mix sodium salt, cyclic ether polymer monomer and plasticizer to obtain liquid precursor electrolyte; S2. Mix the Lewis acid and the chain transfer agent to obtain an initiator-chain transfer mixed solution; S3. The initiator-chain transfer mixed solution is added to the liquid precursor electrolyte, and after mixing evenly, in-situ ring-opening polymerization is carried out to obtain the gel polymer electrolyte.

7. The method according to claim 6, characterized in that, The molar ratio of the sodium salt, cyclic ether polymer monomer, and plasticizer is 1:(11-12):(2.8-2.9); the volume percentage of the plasticizer in the liquid precursor electrolyte is 15%-25%.

8. The method according to claim 6, characterized in that, The volume ratio of the Lewis acid to the chain transfer agent is 1:(80-120); the amount of the initiator-chain transfer mixed solution added is 0.01wt% to 0.015wt% based on the total mass of the liquid precursor electrolyte.

9. The method according to any one of claims 6 to 8, characterized in that, By controlling the type and / or amount of the chain transfer agent, the number of polymer chains, the average chain length, and the degree of interchain entanglement in the ether polymer network generated by the polymerization reaction are increased.

10. An application of a gel polymer electrolyte, characterized in that, The gel polymer electrolyte is the gel polymer electrolyte according to any one of claims 1 to 5, or the gel polymer electrolyte prepared by the method according to any one of claims 6 to 9. The gel polymer electrolyte is used to prepare a low-temperature sodium-ion battery, and the low-temperature sodium-ion battery further includes a positive electrode, a negative electrode, and a separator.